Evaluation of Lacrimal Punctal Changes by Anterior Segment Optical Coherence Tomography after Punctal Dilation Versus Punctal Plug Insertion in Cases of Inflammatory Punctual Stenosis - Islam Awny; Elshimaa A Mateen Mossa; Tasneem Mohammed Bakheet; Hany Mahmoud; Amr Mounir (Journal of Ophthalmology)
Purpose. To compare simple punctal dilation versus punctal dilation augmented by insertion of Punctal Plug Insertion (PPP) with assessing the effect on resolving epiphora and punctum size improvement by an objective method, high-resolution AS-OCT imaging comparing punctal parameters of the patients before and after both techniques. Patients and Methods. It is a prospective, interventional, double-blinded controlled randomized study, which was conducted on two groups of patients, the first epiphora group (EG1 25 eyes), who had acquired punctal stenosis and epiphora and managed by simple punctal dilatation. The second epiphora group (EG2 20 eyes) who managed by punctal dilatation augmented with an application of perforated punctal plugs for two months. Spectral Domain Anterior Segment-OCT Image Acquisition. AS-OCT for lower puncti was performed using RTVue (Optovue Inc., Fermont, CA). OCT images of the width and length of the lower puncti of the participants were captured by the same operator on the same machine. Measuring of punctal size (diameter and length) was performed before treatment, one week, one month, and three months later objectively by using AS-OCT. Results. The study included 45 eyes of 50 subjects; the total coverage of epiphora patients fulfilled inclusion criteria and presented to the ophthalmology clinics of Sohag University Hospitals in the period between June 2021 and December 2021. Both groups were comparable regarding mean age (39 ± 11 vs 50 ± 12 years, P value = 0.4) and sex (males were 36% vs 40%, female were 64% vs 60%, P value = 0.5) respectively with no statistically significant difference between both groups. The mean duration of epiphora was measured in both groups before treatment (EG1 = 1.656 ± 0.41 months, EG2 = 1.73 ± 0.32 months) with no statistically significant difference (P value = 0.436). There was marked improvement of the outer punctual diameter and length between outer and inner puncti in EG1 (EG1 391um ± 122 um, EG2 692 ± 226 um (P value < 0.007) and EG1 189 ± 43 um, 380 ± 169 um (P value < 0.0002) during the follow-up period. EG2 showed more improvement than EG1 when compared during the follow-up period in both outer punctual diameter and length between outer and inner puncti with (P value < 0.003 and < 0.0002) in favor of EG2. However; both groups show improvement with the statistically significant difference in both groups by using AS-OCT. Conclusions. Punctal dilation augmented by insertion of PPP was an effective method in treating cases of inflammatory punctual stenosis as found by monitoring of punctal parameters changes by AS-OCT. AS-OCT was found a useful method for the evaluation of the lacrimal punctal parameters, especially with different treatment modalities in epiphora cases.